Obstructive jaundice with duodenal biliary fistula: diagnostic and therapeutic challenges, case report, and literature review - Xing, Rongchun; Hou, Yiwei; Yi, Li; Wan, Qingjin; Chen, Guoxin; Wang, Yashan; Hu, Mingzheng; Yang, Yu (Frontiers in Medicine, 2025)
BackgroundThis case presents a 56-year-old male with obstructive jaundice, complicated by bile duct stones, bile duct dilation, and a possible biliary-enteric fistula. This case contributes to the literature by highlighting the complexities of managing obstructive jaundice in patients with complex surgical histories.Case summaryThe patient, with a history of laparoscopic cholecystectomy (2022), presented with upper abdominal pain, jaundice, and fever. Imaging (ultrasound, CT, MRCP) revealed intrahepatic bile duct dilation, pneumobilia, stones, and a biliary-enteric fistula. Initial ERCP attempted fistula dilation but was unsuccessful due to inflammatory fibrosis. Subsequent laparoscopic partial gastrectomy with Roux-en-Y gastrojejunostomy resolved the obstruction. Postoperative recovery was uneventful, with resolution of jaundice and scheduled six-month follow-up.ConclusionThis case highlights the critical role of multimodal imaging (MRCP/CT) in diagnosing rare biliary-enteric fistulas, particularly in patients with surgical histories. A multidisciplinary approach—combining endoscopic intervention and tailored laparoscopic surgery—proved effective for managing complex obstructive jaundice. Vigilant postoperative surveillance is essential to mitigate recurrence risks. Future studies should explore minimally invasive techniques for similar cases.